AN ANALYSIS OF COMMUNICATION STRATEGIES USED BY ENGLISH TEACHER AT SUTA DHARMA KINDERGARTEN - ., Ni Wayan Yuni Lisnayanti; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk (1) mengetahui tipe-tipe strategi komunikasi yang digunakan oleh guru Bahasa Inggris di Taman Kanak-Kanak Suta Dharma dalam berkomunikasi dengan siswa, (2) mengetahui strategi komunikasi yang paling banyak digunakan oleh guru Bahasa Inggris dalam berkomunikasi dengan siswa, (3) mengetahui alasan dari guru Bahasa Inggris dalam menerapkan strategi komunikasi tertentu dalam berkomunikasi dengan para siswa. Penelitian ini bersifat kualitaitif. Subyek dari penelitian ini adalah seorang guru Bahasa Inggris yang mengajar pada pelajaran Bahasa Inggris kepada siswa di Taman Kanak-Kanak Suta Dharma. Guru menggunakan lebih dari satu bahasa yaitu bahasa Indonesia dan bahasa Bali di dalam pelajaran Bahasa Inggris. Bahasa Indonesia dan Bahasa Bali digunakan untuk membantu siswa mengerti dengan bahasa yang ingin dicapai. Objek dari penelitian ini adalah strategi komunikasi yang meliputi approximation, circumlocution, massage abandonment, code switch, repetition, literal translation, appeal for assistance, mime, generalization, drawl, reconstruction, topic avoidance, dan word coinage. Hasil dari penelitian ini memperlihatkan bahwa guru menerapkan delapan dari tiga belas strategi komunikasi dalam pengajaran Bahasa Inggris di Taman Kanak-Kanak Suta Dharma yaitu : topic avoidance, message abandonment, code switch, approximation, circumlocution, repetition, literal translation, dan mime. Strategi komunikasi yang paling banyak digunakan oleh guru Bahasa Inggris adalah code switch. Terdapat dua alasan mengapa guru di Suta Dharma Kindergarten menerapkan startegi komunikasi yaitu (1) untuk membuat para siswa mengerti tentang apa yang guru ucapkan dan (2) kurangnya kemampuan Bahasa Inggris dari guru tersebut. Kata Kunci : komunikasi, strategi komunikasi, bilingual This study aimed at finding out (1) the types of communication strategies which were used by the English teacher at Suta Dharma Kindergarten in communicating with students, (2) the communication strategy which was most frequently used by English Teacher in communicating with students, (3) English teacher’s reasons in applying the communication strategies to communicate with students. This study was qualitative. The subject of this study was an English teacher who taught the English lesson to the students at Suta Dharma Kindergarten. The teacher used more than one language which were Indonesian and Balinese in teaching English. Indonesian and Balinese were used to help the students understand the target language. The object of this study was communication strategies which included approximation, circumlocution, massage abandonment, code switch, repetition, literal translation, appeal for assistance, mime, generalization, drawl, reconstruction, topic avoidance, and word coinage. The results of this study showed that the teacher applied eight out of thirteen of communication strategies in teaching English at Suta Dharma Kindergarten that had been observed, namely: topic avoidance, message abandonment, code switch, approximation, circumlocution, repetition, literal translation, and mime. The communication strategy that was most frequently used by the English teacher was code switch. There were two reasons why the teacher at Suta Dharma Kindergarten applied the communication strategies. The reasons were (1) making the students understand about what the teacher said and (2) lack of the teacher English ability. keyword : communication, communication strategies, bilingual